Does the Interaction between Local and Systemic Inflammation Provide a Link from Psychology and Lifestyle to Tissue Health in Musculoskeletal Conditions? - David M. Klyne (International Journal of Molecular Sciences, 2021)
Musculoskeletal conditions are known to involve biological, psychological, social and, often, lifestyle elements. However, these domains are generally considered in isolation from each other. This siloed approach is unlikely to be adequate to understand the complexity of these conditions and likely explains a major component of the disappointing effects of treatment. This paper presents a hypothesis that aims to provide a foundation to understand the interaction and integration between these domains. We propose a hypothesis that provides a plausible link between psychology and lifestyle factors with tissue level effects (such as connective tissue dysregulation/accumulation) in musculoskeletal conditions that is founded on understanding the molecular basis for interaction between systemic and local inflammation. The hypothesis provides plausible and testable links between mind and body, for which empirical evidence can be found for many aspects. We present this hypothesis from the perspective of connective tissue biology and pathology (fibrosis), the role of inflammation locally (tissue level), and how this inflammation is shaped by systemic inflammation through bidirectional pathways, and various psychological and lifestyle factors via their influence on systemic inflammation. This hypothesis provides a foundation for new consideration of the development and refinement of personalized multidimensional treatments for individuals with musculoskeletal conditions.